DEVELOPMENT TENDENCIES OF MARKETING PERSONNEL MANAGEMENT UNDER THE FOURTH INDUSTRIAL REVOLUTION - TELNOV, Anatoliy; RESHMIDILOVA, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to analyze the general features, technologies, risks and threats of the fourth industrial revolution, to justify changes in the educational and professional system on the development trends of personnel marketing management, taking into account the identified trends. The article defines the content and components of Industry 4.0. The problems that arise as a result of the development of the fourth industrial industry are identified, namely: "extinction of jobs" and "change of skills". The "Industry 4.0 in Ukraine" movement was analyzed. The change of professions and types of activities in connection with technological and innovative development is analyzed. An analysis of the professions most and least prone to automation was carried out. It was determined that in the near future, professions that require social and creative skills, in particular, decision-making in conditions of uncertainty and the development of innovative ideas, will have a low risk of automation. Complex problem solving, communication skills, and systems skills will be in higher demand than physical abilities or content creation skills. The role of marketing management of personnel in the conditions of the fourth industrial revolution is substantiated. The requirements for personnel marketing management and the tasks of HR marketing at enterprises are defined. The main task of marketing management is determined, which consists in achieving a feeling of satisfaction with all parties to the exchange. It is justified that the education system is changing in accordance with the requirements of 4PR, the concept of education 4.0 is being formed, the content of which is determined through practical innovative activity. Indicators of educational transformations will be: changes in technologies, globalization, a new generation of young people who will live mostly in the virtual world, cultural and social diversity, new skills and competences, forms, means and technologies of learning, lifelong learning (LLL). The changes in the education system and directions of training of modern specialists are characterized, taking into account digital technologies and global communication infrastructure. Some measures of personnel marketing management under the conditions of adaptation to the requirements of the fourth industrial revolution are proposed.